2011
DOI: 10.6017/ital.v30i1.3043
|View full text |Cite
|
Sign up to set email alerts
|

Web Accessibility, Libraries, and the Law

Abstract: With an abundance of library resources being served on the web, researchers are finding that disabled people oftentimes do not have the same level of access to materials as their nondisabled peers. This paper discusses web accessibility in the context of United States’ federal laws most referenced in web accessibility lawsuits. Additionally, it reveals which states have statutes that mirror federal web accessibility guidelines and to what extent. Interestingly, fewer than half of the states have adopted statut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…For example, although the American Library Association Council approved a policy on services to patrons with disabilities (Burke, ), many libraries do not have full‐time staff available to assist them, do not fully train staff on their access needs and how to provide assistive technologies, and do not have their own policies for serving patrons with disabilities (Myhill, Hill, Link, Small, & Bunch, ; Wiler & Lomax, ). Subsequently, many households with people with disabilities report that libraries are inaccessible, and physical accessibility may be better than access through assistive technology (Burke, ; Fulton, ). Related, researchers have found that state governments are not meeting the needs of people with disabilities in the way information is presented on websites (Rubaii‐Barrett & Wise, ).…”
mentioning
confidence: 99%
“…For example, although the American Library Association Council approved a policy on services to patrons with disabilities (Burke, ), many libraries do not have full‐time staff available to assist them, do not fully train staff on their access needs and how to provide assistive technologies, and do not have their own policies for serving patrons with disabilities (Myhill, Hill, Link, Small, & Bunch, ; Wiler & Lomax, ). Subsequently, many households with people with disabilities report that libraries are inaccessible, and physical accessibility may be better than access through assistive technology (Burke, ; Fulton, ). Related, researchers have found that state governments are not meeting the needs of people with disabilities in the way information is presented on websites (Rubaii‐Barrett & Wise, ).…”
mentioning
confidence: 99%
“…This legislation has not been overlooked by the profession, and many articles that address issues related to library accessibility also evaluate the meaning and impact of federal disability laws on library collections and services (Providenti & Zai, 2007;Schmetzke & Comeaux, 2009;Southwell & Slater, 2012;Stewart, Schmetzke, & Narenda, 2005;Tatomir & Durrance, 2010). Fulton (2011) is one of the few authors to systematically examine state web accessibility statutes as they relate to libraries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The importance of applying Web accessibility standards to online library resources has been-and continues to be-discussed in library literature (Bickner, 2002;Coonin & Hines, 2012;Fichter, 2013;Fulton, 2011;Providenti & Zai, 2007;Riley-Huff, 2012;Schmetzke & Comeaux, 2009). However, librarians may be creating content for online courses without the training necessary to understand how to make instructional materials accessible to all students.…”
Section: Application To Library Resourcesmentioning
confidence: 99%